THE DEVELOPMENT OF DIGITAL ECONOMY TECHNOLOGIES AND IMPLEMENTATION OF MANUFACTURING EXECUTION SYSTEMS - Gorokhova, Anna; Goncharov, Vitaly; Stepanova1, Diana; Zvereva, Tatyana; Valigursky, Dmitry (Revista Inclusiones, 2020)
Modern production is aimed at maximum productivity and manufacturability. The latter is a decisive factor in the competition for sales markets and, as a consequence, for the profit and enterprises development. In a post-industrial society, which every economy of the 21st century must build and accept, the most important advantage is the use of high technologies to manage modern manufacturing systems. The article is devoted to the problem of digital economy technologies for managing modern manufacturing systems. A theoretical analysis of the patterns of using digital technologies in managing manufacturing systems is carried out. Based on the results of the expert survey, new functionality and potential effects of the use of digital economy technologies for managing manufacturing systems are identified. A hierarchy model of managing a manufacturing system using digital technologies is presented.